PENERAPAN KEBIJAKAN PENANGANAN TINDAK KEKERASAN PEREMPUAN DI DINAS PEMBERDAYAAN PEREMPUAN DAN PERLINDUNGAN ANAK KOTA PALU - Daniel T. Todapa; Juemi Juemi (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Implementation of the policy of handling acts of violence against women in the women's empowerment and child protection office of Palu City. using a qualitative research basis with a descriptive approach, while data collection techniques are carried out by observation, interviews, and documentation. The data used in this study are primary data and secondary data. The determination of informants in this study used purposive by determining 4 (people) informants. Data analysis in this study is data reduction, data presentation, and drawing conclusions. The theory used in this study is the theory by Donald Van Metter and Carl Van Horn, there are 6 aspects that need to be considered, namely 1) standards, targets, and objectives of the policy, 2) resources, 3) characteristics of the implementing organization, 4) communication between implementing organizations, 5) attitudes of implementers, and 6) economic, social, and political environment. The results of the study concluded that the factors that caused the implementation of the policy of handling acts of violence against women to be less than optimal were the lack of information or socialization to the community regarding the prevention and handling of acts of violence due to the lack of budget in handling acts of violence against women, and the unavailability of UPTD to support the handling of acts of violence against women.